Transcriptomic analysis of Bifidobacterium longum subsp. longum BBMN68 in response to oxidative shock. Issue 1 (December 2018) - Zuo, Fanglei; Yu, Rui; Xiao, Man; Khaskheli, Gul; Sun, Xiaofei; Ma, Huiqin; Ren, Fazheng; Zhang, Bing; Chen, Shangwu
Abstract Bifidobacterium longum strain BBMN68 is sensitive to low concentrations of oxygen. A transcriptomic study was performed to identify candidate genes forB. longum BBMN68's response to oxygen treatment (3%, v/v). Expression of genes and pathways ofB. longum BBMN68 involved in nucleotide metabolism, amino acid transport, protein turnover and chaperones increased, and that of carbohydrate metabolism, translation and biogenesis decreased to adapt to the oxidative stress. Notably, expression of two classes of ribonucleotide reductase (RNR), which are important for deoxyribonucleotide biosynthesis, was rapidly and persistently induced. First, the class Ib RNR NrdHIEF was immediately upregulated after 5 min oxygen exposure, followed by the class III RNR NrdDG, which was upregulated after 20 min of exposure. The upregulated expression of branched-chain amino acids and tetrahydrofolate biosynthesis-related genes occurred in bifidobacteria in response to oxidative stress. These change toward to compensate for DNA and protein damaged by reactive oxygen species (ROS). In addition, oxidative stress resulted in improvedB. longum BBMN68 cell hydrophobicity and autoaggregation. These results provide a rich resource for our understanding of the response mechanisms to oxidative stress in bifidobacteria.